Um eclesiástico-mestre nos sertões: reconstituição da trajetória de um eclesiástico-mestre de índios dos sertões do leste de Minas Gerais (1750-1801) - Bruno Duarte Guimaraes Silva (2017)
This present dissertation is a result of historical research to reconstruct the trajectory of João Pedro de Almeida. A ecclesiastic-teacher who served in indigenous villages in the sertões of the east region from the captaincy of Minas Gerais in the last two decades of the eighteenth century. This work aims to assemble knowledge from the documented particular trajectory of this individual and how it is related to social processes of consolidation of the regal education system. The implications of his work on colonial frontier expansion toward to sertão of the captaincy is explored as well. The documental research indicates that João Pedro was a mestiço, son of a former slaved woman and non-identified man. This configuration usually did not allow a person to hold the position he held according to rules of clerical recruiting based on Portuguese colonial social standards. However, the research shows that the colonial frontier expansion process and the regal education consolidation in Minas Gerais occasioned normative gaps for the strategic services according to colonial goals. Toward to colonial frontier expansion, aside from the warfare against indigenous peoples, the cultural assimilation was applied as a method as well. The João Pedros literacy and availability to work teaching indigenous were fundamental to overcome his birth status that was expected to be a severe drawback to his ordination as a ecclesiastic. This dissertation presents the methods and theatrical bases that guides the documental research and its findings treatment. Thus, this particular life trajectory study contributes by enlarging knowledge about colonial frontier expansion processes in Minas Gerais and regal education system for indigenous.